2018
DOI: 10.1097/fch.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Health Promotion Program on Rural, West Virginia Adults

Abstract: This health promotion project is a 12-week program for adults in a rural West Virginia community with a body mass index (BMI) of 25 or greater. The goals of this project were to facilitate learning through modules focusing on activity and nutrition, increase knowledge of healthy activity and nutrition, and improve weight and BMI. Each 12-week session provided evidenced-based information regarding obesity, physical activity, and nutrition. Participants completed pre- and postprogram and 1-month follow-up survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Two studies were conducted in Australia, and one was conducted in Europe and South America. Most of the studies (44.4%) were conducted in the community setting (Arevalo & Brown, 2019;Armitage, Alganem & Norman, 2017;Tucker et al, 2019;Choo & Kang, 2015;Ekúndayò et al, 2020;Griffin et al, 2018;Hales et al, 2016;Kite et al, 2018;Powers et al, 2019;Schifferdecker et al, 2016;Spurrier et al, 2018;Vandelanotte et al, 2018). In comparison, five (18.5%) were conducted in the workplace (Abdi et al, 2015a;Abdi et al, 2015b;Ott et al, 2015;Sanaeinasab et al, 2020;Silberman et al, 2020) and institutional settings, respectively (Dong & Branscum, 2019;Johnson & Annesi, 2017;Romain, Horwath & Bernard, 2018;Saghafi-Asl, Aliasgharzadeh & Asghari-Jafarabadi, 2020;Wright et al, 2020); three (11.1%) in a health care setting (de Menezes et al, 2015;Nazari et al, 2019;Winik & Bonham, 2018); and one each in a church (Lin et al, 2015) and a sports centre (Cingil & Göger, 2020).…”
Section: Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were conducted in Australia, and one was conducted in Europe and South America. Most of the studies (44.4%) were conducted in the community setting (Arevalo & Brown, 2019;Armitage, Alganem & Norman, 2017;Tucker et al, 2019;Choo & Kang, 2015;Ekúndayò et al, 2020;Griffin et al, 2018;Hales et al, 2016;Kite et al, 2018;Powers et al, 2019;Schifferdecker et al, 2016;Spurrier et al, 2018;Vandelanotte et al, 2018). In comparison, five (18.5%) were conducted in the workplace (Abdi et al, 2015a;Abdi et al, 2015b;Ott et al, 2015;Sanaeinasab et al, 2020;Silberman et al, 2020) and institutional settings, respectively (Dong & Branscum, 2019;Johnson & Annesi, 2017;Romain, Horwath & Bernard, 2018;Saghafi-Asl, Aliasgharzadeh & Asghari-Jafarabadi, 2020;Wright et al, 2020); three (11.1%) in a health care setting (de Menezes et al, 2015;Nazari et al, 2019;Winik & Bonham, 2018); and one each in a church (Lin et al, 2015) and a sports centre (Cingil & Göger, 2020).…”
Section: Study Findingsmentioning
confidence: 99%
“…Table 2 presents the characteristics of the included studies and health assessments reported. The included studies employed different study designs, including 17 (63.0%) experimental studies such as pre-and post-intervention (Arevalo & Brown, 2019;Tucker et al, 2019;Spurrier et al, 2018;Wright et al, 2020); pretest and post-test (Griffin et al, 2018; Exercise and sleep quality and quantity. Powers et al, 2019;Winik & Bonham, 2018); randomised controlled trials (Abdi et al, 2015b;Armitage et al, 2017;de Menezes et al, 2015;Hales et al, 2016;Lin et al, 2015;Sanaeinasab et al, 2020;Vandelanotte et al, 2018); quasi-experimental (Cingil & Göger, 2020;Schifferdecker et al, 2016); and treatment (Johnson & Annesi, 2017).…”
Section: Study Findingsmentioning
confidence: 99%
“…To improve population health outcomes, broad‐based partnerships are needed to address the myriad factors and determinants operating in these environments which contribute to health disparities (Cancel‐Tirado, Feeney, Washburn, Greder, & Sano, ). In rural areas, greater disparities are generally encountered due to poverty, education, rural attitudes and culture, and lack of or greater geographic dispersion of resources (Clark et al, ; Spurrier, Suttle, Matheson, & Baker‐Watson, ). Despite growing emphasis on reducing rural health disparities, adults living in rural areas remain at increased risk of adverse health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite growing emphasis on reducing rural health disparities, adults living in rural areas remain at increased risk of adverse health outcomes. Compared to their urban counterparts, rural Americans have higher rates of chronic conditions including obesity, diabetes, and cardiovascular disease, and are more likely to engage in health‐risk behaviors including tobacco use, poor dietary intake, and physical inactivity (Clark et al, ; Lichter, Parisi, & Taquino, ; Meit et al ; Spurrier et al, ). Additionally, many rural counties face challenges secondary to Hispanic population growth (Lichter et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation